Minat Petani Jagung Dalam Pembentukan Kelompok Tani Di Desa Sokawera, Somagede, Banyumas - Damar Jati; Sodik Dwi Purnomo; Diah Retnowati (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
The food crop sector has a major contribution to national economic growth. For small farmers, farmer group institutions are very effective in developing farming businesses, but many farmers are not yet incorporated into farmer groups. This study aims to find out the factors that influence the interest of farmers to join farmer groups in Sokawera Village, Somagede District, Banyumas. This research is a quantitative type with primary data obtained from questionnaires, interviews and observations of 75 respondents. The analysis used is logistic regression to find the effect of the variables of business income, education level, land area, length of business, number of family dependents, age, and technology on interest in forming farmer groups. The results obtained are income, education, land area, number of family dependents, and age affect the interest of farmers to join farmer groups in Sokawera Village. Based on the results of this study, it is expected that the role of the government and farmer group institutions in socialization is strengthened to increase.